2023
DOI: 10.3390/v15071507
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Host Cell Surface Glycan Structure for Cell Specificity of Influenza A Viruses

Abstract: Influenza A viruses (IAVs) initiate infection via binding of the viral hemagglutinin (HA) to sialylated glycans on host cells. HA’s receptor specificity towards individual glycans is well studied and clearly critical for virus infection, but the contribution of the highly heterogeneous and complex glycocalyx to virus–cell adhesion remains elusive. Here, we use two complementary methods, glycan arrays and single-virus force spectroscopy (SVFS), to compare influenza virus receptor specificity with virus binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In this study, the anti-influenza activity of an algal lectin, HBL40, was demonstrated by an in vitro experiment using cultured human cells and the influenza virus A/H3N2/Udorn/72. On the other hand, it is important to examine the in vivo inhibitory effect of the lectin because the local organization and environment of the receptors or other cell surface molecules may alter the binding specificity of the lectin [27]. Furthermore, the infections of influenza viruses are affected by heterologous polarized cells with virus receptors in the respiratory tract, which form an apical surface facing the external environments and a basal surface attached to the basement layer [28].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the anti-influenza activity of an algal lectin, HBL40, was demonstrated by an in vitro experiment using cultured human cells and the influenza virus A/H3N2/Udorn/72. On the other hand, it is important to examine the in vivo inhibitory effect of the lectin because the local organization and environment of the receptors or other cell surface molecules may alter the binding specificity of the lectin [27]. Furthermore, the infections of influenza viruses are affected by heterologous polarized cells with virus receptors in the respiratory tract, which form an apical surface facing the external environments and a basal surface attached to the basement layer [28].…”
Section: Discussionmentioning
confidence: 99%